2005
DOI: 10.1001/archinte.165.22.2601
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work-Hour Limitations on Resident Well-being, Patient Care, and Education in an Internal Medicine Residency Program

Abstract: Internal medicine residents approve of WHLs overall and report benefits to their well-being. However, they also report negative effects on patient care and resident education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(175 citation statements)
references
References 47 publications
5
161
2
6
Order By: Relevance
“…In this systematic review and meta-analysis of 19 studies enrolling 2030 residents, we found that 1 intervention, limiting resident hours, was consistently associated with a decreased emotional exhaustion component of burnout [12][13][14]21 and lower overall burnout rates. 15 Other interventions were examined in a few studies that enrolled small numbers of residents.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In this systematic review and meta-analysis of 19 studies enrolling 2030 residents, we found that 1 intervention, limiting resident hours, was consistently associated with a decreased emotional exhaustion component of burnout [12][13][14]21 and lower overall burnout rates. 15 Other interventions were examined in a few studies that enrolled small numbers of residents.…”
Section: Discussionmentioning
confidence: 82%
“…15,16 Several studies reported on more than 1 dimension of the MBI. Improvement in emotional exhaustion was reported in 4 studies, [12][13][14]21 improvement in depersonalization was reported in 1 study, 19 and improvements in personal achievement was reported in 1 study. 10 Only 1 of the 2 studies reported the overall burnout score and significant improvement, although the direction of the effect was the same in both studies.…”
Section: Qualitative Synthesis Of Datamentioning
confidence: 97%
See 1 more Smart Citation
“…94 However, other aspects of well-being such as rates of depression do not seem to have changed between the pre-2003 period and the post-2003 period. 21,22,36,95 Prior research has demonstrated links between resident well-being and quality of patient care, 96,97 making preservation of resident well-being extremely important. This improvement in well-being may be one explanation for why some patient care parameters are improving in the post-2003 time period.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of burnout did not statistically significantly worsen in any study, although there was a nonsignificant worsening in one study. 21 Burnout improved in five studies, 22,30,36,51,54 most often as a result of a decrease in emotional exhaustion. Two studies found that a higher number of work hours was related to burnout.…”
Section: The 2003 Duty Hour Rules and Resident Well-beingmentioning
confidence: 95%